A systematic approach to weaning from extracorporeal membrane oxygenation in patients with refractory cardiac failure. Issue 7 (27th March 2021) - Mørk, Sivagowry R.; Frederiksen, Christian A.; Nielsen, Roni R.; Lichscheidt, Emil; Christensen, Steffen; Greisen, Jacob R.; Tang, Mariann; Vase, Henrik; Løgstrup, Brian B.; Mellemkjær, Søren; Wiggers, Henrik S.; Mølgaard, Henning; et al.
Abstract : Background: Veno‐arterial extracorporeal membrane oxygenation (V‐A ECMO) is commonly used to provide haemodynamic support for patients with severe cardiac failure. However, timing ECMO weaning remains challenging. We aimed to examine if an integrative weaning approach based on predefined haemodynamic, respiratory and echocardiographic criteria is associated with successful weaning. Methods: All patients weaned from ECMO between April 2017 and April 2019 at Aarhus University Hospital, Denmark, were consecutively enrolled. Predefined haemodynamic, respiratory and echocardiographic criteria were assessed before and during ECMO flow reduction. A weaning attempt was commenced in haemodynamic stable patients and patients remaining stable at minimal flow were weaned from ECMO. Comparisons were made between patients who met the criteria for weaning at first attempt and patients who did not meet these criteria. Patients completing a full weaning attempt with no further need for mechanical support within 24 h were defined as successfully weaned. Results: A total of 38 patients were included in the study, of whom 26 (68%) patients met the criteria for weaning. Among these patients, 25 (96%) could be successfully weaned. Successfully weaned patients were younger and had less need for inotropic support and ECMO duration was shorter. Fulfilling the weaning criteria was associated with successful weaning and both favourable 30‐d survival and survival to discharge. Conclusion: An integrative weaning approach based on haemodynamic, respiratory and echocardiographic criteria may strengthen the clinical decision process in predicting successful weaning in patients receiving ECMO for refractory cardiac failure.